Synergistic effects of A-B-C-type amphiphilic copolymer on reversal of drug resistance in MCF-7/ADR breast carcinoma - Zhang L (Dove Medical Press, 2016)
Lu Zhang,1–3 Jiafei Lu,3 Liyan Qiu1 1Ministry of Education (MOE) Key Laboratory of Macromolecular Synthesis and Functionalization, Department of Polymer Science and Engineering, Zhejiang University, Hangzhou, 2Drug Clinical Trial Office, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 3College of Pharmaceutical Sciences, Zhejiang University, Hangzhou, People’s Republic of China Abstract: P-glycoprotein (P-gp) overexpression has become the most common cause of occurrence of multidrug resistance in clinical settings. We aimed to construct a micellar polymer carrier to sensitize drug-resistant tumors to doxorubicin (DOX). This A-B-C-type amphiphilic copolymer was prepared by the sequential linkage of β-cyclodextrin, hydrophobic poly(D,L-lactide), and hydrophilic poly(ethylene glycol). Upon incubation of the DOX-loaded micelles with DOX-resistant human breast carcinoma MCF-7/ADR cells, significantly enhanced cytotoxicity and apoptosis were achieved. A series of studies on the action mechanism showed that the polymer components such as β-cyclodextrin, hydrophobic poly(D,L-lactide) segment, and poly(ethylene glycol) coordinatively contributed to the improved intracellular ATP depletion and ATPase activity, increased intracellular uptake of P-gp substrates via competitive binding to P-gp, and decreased P-gp expression in MCF-7/ADR cells. More interestingly, a similar phenomenon was observed in the zebrafish xenograft model, resulting in ~64% inhibition of MCF-7/ADR tumor growth. These results implied that the polymeric micelles displayed great potentials as P-gp modulators to reverse DOX resistance in MCF-7/ADR breast carcinoma. Keywords: multidrug resistance, P-glycoprotein, micelle, doxorubicin, zebrafish